STRATEGIC STUDY OF INFRASTRUCTURE DEVELOPMENT ON THE ECONOMY OF MICRO, SMALL, AND MEDIUM ENTERPRISES IN TEBING TINGGI CITY FROM AN ISLAMIC LAW PERSPECTIVE - Tarigan, Tetty Marlina; Rizal, M. (AT-TAFAHUM: Journal of Islamic Law, 2024)
Economic improvement is a method or process with various efforts to make humans have power and strength as a continuous process to build their living abilities. The development of better infrastructure such as internal communications is an example of the importance of coordination for development, including decentralizing the role and authority of developing a joint framework. The aim of this research is to determine the strategic impact of infrastructure development on the economic level of the Micro, Small and Medium Enterprises community in Tebing Tinggi city from an Islamic legal perspective. This research method is qualitative research, namely research that uses both deductive and inductive inference processes as well as analytical analysis of the dynamics of relationships between analytical and analytical methods which are researched using scientific logic. The introduction of qualitative research is mainly based on carrying out the research process through formal analytical thinking principles. The results of the research are that the availability of infrastructure is one of the factors driving regional productivity. Economic growth in the city of Tebing Tinggi has not been inclusive. Infrastructure development in the city of Tebing Tinggi encourages economic growth, road infrastructure increases access to employment opportunities and more equal distribution of income.